Prediction of water flux using excel for different modification methods in forward osmosis membrane fabrication - Mun, Tang Pui; Mazrul Nizam, Abu Seman (AIP Publishing, 2023)
Recently, forward osmosis (FO) is developed rapidly and widely used in many applications such as water treatment and food processing. This research is aim to predict and compare the water flux (Jw) of modified membranes by different modification methods which are interfacial polymerization (IP), layer by layer (LbL) and UltraViolet-photografting (UVP) by a suitable model at vary osmotic pressure of draw solution. Predicted water flux of modified membranes under a different range of osmotic pressure (pD) of draw solution were generated by Microsoft Excel from the water flux model with the consideration effects of internal concentration polarization (ICP) which expressed by reverse salt diffusion (RSD). The predicted Jw of each membrane was analyzed and compared. Overall, the predicted Jw increases with the pD. The membranes modified by interfacial polymerization shows the good predicted Jw among the modification methods with IP 1 ranges from 13.07 LMH to 23.35 LMH while IP2 ranges from 24.90 LMH to 25.02 LMH. LbL 2 has the highest predicted Jw among the modified membranes at 44.34 LMH. In conclusion, the theoretical water flux model is capable to predict the water flux of modified membranes. Optimum modification parameters of membrane can be determined from the predicted water flux generated by the model.